Structural, optical, electrical, and photocatalytic application of NiFe2O4@NiO nanocomposites for methylene blue dye. (1st May 2023) - Tripta,; Rana, Pawan S.
Abstract: In this work, the structural, dielectric, and optical properties of NiFe2 O4 @NiO (1:0, 0.9:0.1, 0.7:0.3, 0.5:0.5, and 0:1) nanocomposites using co-precipitation process for its possible application in wastewater treatment. Structural properties have been studied using X-ray powder diffraction (XRD) and FTIR spectroscopy, and morphology by transmission electron microscopy (TEM). From XRD analysis of NiFe2 O4 and NiO nanocomposites revealed the origination of cubic structure. TEM images revealed that the particle size increased with nickel oxide content. The oxidation state was elucidated from X-ray photoelectron spectroscopy (XPS). Real (Z′) and imaginary (Z″) part of impedance, dielectric constant ( ε ′), dielectric loss ( ε ″), ac conductivity (σac ) was studied with frequency (1Hz −10 MHz), and composition. ε ′, ε ″ and σac were observed to increase with nickel oxide concentration. At tetrahedral sites, the hopping of electrons between Fe 2+ and Fe 3+ ions may be due to concentration variation. The Nyquist plot showed two semicircle arcs which represent the effect of grains and grains boundary in conduction. The photocatalytic activity was executed for methylene blue dye up to 95.41% of dye degradation was attained within 120 min for (0.5NiFe2 O4 /0.5NiO) nanocomposite.